IN THE REPUBLIC OF UZBEKISTAN, THE BASIS OF THE MORAL AND MORAL PRINCIPLES OF WORKING PERSONNEL AND THE THEORY OF THEIR STUDY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In this article, the retrospective basis of the spiritual and moral principles of the civil servant and our analyzes aimed at the importance of their study make it possible to develop the following patterns on the topic: first, the retrospective basis of the spiritual principles of the civil servant in the management of the state and society and the importance of their study.